(untitled) (Economics and region, 2023)
The purpose of the study is to analyse the indicators of the development of the fintech market in Ukraine and to build a predictive trend model of the number of fintech companies created in 2023. The methods of analysis and extrapolation of trends were used to conduct the study. The factors influencing the active development of financial technologies in Ukraine are listed, as well as the main problems in the development of fintech. Indicators of the dynamics of creation of domestic fintech companies in 2012-2022 are given. The distribution of fintech companies by sector of activity has been analysed. The sources of financing of fintech companies in 2023 were studied. The range of technologies used by Ukrainian fintech companies was studied. Five trend models were created to forecast the number of fintech companies created in Ukraine in 2023.